Human glutathione S-transferases : characterization, tissue distribution and kinetic studies - Corrigall, Anne Vint (UCT/MRC Liver Research Centre, 2018)
In this study the purification of human basic and near-neutral liver, and human basic and acidic lung glutathione S-transferases (GSH S-T) was undertaken. Purification of the basic and near-neutral GSH S-T was achieved using a combination of affinity chromatography, chromatofocusing and immunoaffinity chromatography. Affinity and ion exchange chromatography were employed in the purification of the basic and acidic lung forms. The purified proteins had similar physicochemical characteristics to the GSH S-T purified by others. The binding of 1-chloro-2,4-dinitrobenzene (CDNB) to the 3 classes of human GSH S-T, viz. basic, near-neutral and acidic and the effects of such binding, if any, were examined. Human acidic lung GSH S-T is irreversibly inactivated by CDNB in the absence of the co-substrate glutathione (GSH). The time-dependent inactivation is pseudo-first order and demonstrates saturation kinetics, suggesting that inactivation occurs from an EI complex. GSH protects the enzyme against CDNB inactivation. In contrast, the basic and near-neutral GSH S-T are not significantly inactivated by CDNB. Incubation with [¹⁴C]-CDNB indicated covalent binding to all 3 classes of GSH S-T. When the basic and acidic GSH S-T were incubated with [¹⁴C]-CDNB and GSH, cleaved with cyanogen bromide, and chromatographed by HPLC, a single peptide fraction was found to be labelled in both classes. Incubation in the absence of GSH yielded 1 and 2 additional labelled peptide fractions for the basic and acidic transferases, respectively. These results suggest that while CDNB arylates all 3 classes of human GSH S-T, only the acidic GSH S-T possesses a specific GSH-sensitive CDNB binding site, which when occupied leads to time-dependent inactivation of the enzyme. The tissue distribution and localization of the 3 classes of human GSH S-T in normal and tumour tissue was examined. Antibodies to representatives of the 3 classes were raised in rabbits, and radial immunodiffusion employed to quantitate their concentrations in the cytosol of 18 organs from 9 individuals. The data provide the first direct, quantitative evidence for the inter-individual and inter-organ variation suggested by earlier workers. The absence of the near-neutral GSH S-T in 5 of the 9 individuals studied confirms an earlier suggestion of a "null" allele for this transferase. Basic and acidic GSH S-T (apart from in a single liver), were always present. Near-neutral GSH S-T, when present, were found in all tissues examined. The marked inter-organ and inter-individual variation observed in this study may explain individual and organ susceptibility to drugs, toxins and carcinogens. The immunohistochemical localization of the 3 classes of GSH S-T reveals important differences in their localization, and may provide insight into their functions in various organs and tissues.